Dual antiviral therapy for HIV and hepatitis C – drug interactions and side effects. (September 2015) - Esposito, Isabella; Labarga, Pablo; Barreiro, Pablo; Fernandez-Montero, José V; de Mendoza, Carmen; Benítez-Gutiérrez, Laura; Peña, José M; Soriano, Vicente
Abstract : Introduction: Roughly 20% of HIV-positive persons worldwide are coinfected with hepatitis C virus (HCV). The recent advent of direct-acting antivirals (DAA) that cure most hepatitis C patients has attracted much attention. Knowledge on drug interactions between DAA and antiretrovirals (ARV) may allow maximizing antiviral efficacy while minimizing drug-related toxicities. Areas covered: We review the most frequent side effects and clinically significant drug interactions between DAA and ARV. We further discuss how they can be prevented and managed in HIV/HCV-coinfected patients. Expert opinion: The safety profile of current DAA and the most recently approved ARV is quite favorable. Interactions between DAA and ARV could be frequent in clinical practice. The most common drug interactions affect drug metabolism by inducing or inhibiting the cytochrome P450 system, leading to abnormal drug exposures. Throughout this mechanism HCV and HIV protease inhibitors interact, especially when co-formulated with ritonavir as a pharmacoenhancer, and non-nucleoside HCV and HIV polymerase inhibitors. In contrast, HIV and HCV nucleos(t)ide polymerase inhibitors, and most HCV NS5A inhibitors (i.e., ledipasvir) and HIV integrase inhibitors (i.e., dolutegravir), do not or only marginally affect CYP450, and therefore are free of significant drug interactions. Exposure to HIV and HCV nucleos(t)ide analogues (i.e., tenofovir and sofosbuvir, respectively) is subject to induction/inhibition of drug transporters (i.e., P-glycoprotein).